FOLLICULAR DYNAMICS DURING ESTROUS CYCLE IN POSTPUBERTAL AND POSTPARTUM GIR CATTLE - Hadiya, KK; DHAMI, A J; PATEL, J A; LUNAGARIYA, P M (The Indian Journal of Animal Reproduction, 2022)
The follicular dynamics of an entire estrous cycle was monitored daily between two consecutive estruses in 6 postpubertal Gir heifers and 6 postpartum Gir cattle using an ultrasound. The Gir heifers indicated the presence of 2- follicular wave (n=4) and 3-wave (n=2) estrous cycle. The second wave appeared earlier with 3-wave than with 2-wave (p
Keywords: Dominant follicle; Estrous cycle; Follicular dynamics; Follicular waves; gir